TV political advertising and its role in determining the choices of the Iraqi voter in the 2010 legislative elections ((A field study in Baghdad governorate)) (Journal of the College of Basic Education, 2022)
Political advertisement is the most effective form of political communication on people and societies.Particularly on the voter during the election seasons, as it is considered the means through which the candidate canThe politician must achieve his goals and objectives, and political advertisements are based on marketing candidates to an audiencevoters through print, audio and visual mass communication as well as a networkThe Internet, so it always includes elements of attraction and excitement to achieve the desired goal, which is to raise the balance of